Strava: participatory culture and community engagement of rocc members - Epranata, Daniel Rian; Bangun, Cendera Rizky (Jurnal Komunikasi Profesional, 2022)
The Rogue Cycling community is a road bike community that is experiencing the development of online member communication interaction activities. The interaction process generated offline is now getting support through Strava as the new online-based media. Rapid development of communication technology has created a new era where people can interact without the limitations of space and time. The potential use of Strava's new media is considered not only to be a participant, but also to shape the process of creating meaning. New media are also believed to have abilities that resemble interpersonal communication. Strava was formed in order to connect people with the community to increase interaction with each other through the features provided. This study aims to determine the participatory cultural components that make up the Rogue Cycling community in building the involvement of each member through Strava. This research uses case study method with qualitative descriptive research. The results showed that Rogue Cycling involving Strava's new media when analyzed using the concept of participatory culture (affiliations, expression, collaborative problem-solving, and circulation) had reached the four stages of participatory culture based on the formation of virtual Rogue Cycling community in Strava. Such as participated in upload cycling trails with members or carried out the circulation cycling trail process during cycling practice. The essence of participation through the support of the community concept and community involvement also shows that cycling activities cannot be done without a meeting, but virtual community activities and real communities make important contributions to the community. Keywords: Community Engagement, Digital Communication, Participatory Culture, ROCC Community, Strava. The Rogue Cycling community is a road bike community that is experiencing the development of online member communication interaction activities. The interaction process generated offline is now getting support through Strava as the new online-based media. Rapid development of communication technology has created a new era where people can interact without the limitations of space and time. The potential use of Strava's new media is considered not only to be a participant, but also to shape the process of creating meaning. New media are also believed to have abilities that resemble interpersonal communication. Strava was formed in order to connect people with the community to increase interaction with each other through the features provided. This study aims to determine the participatory cultural components that make up the Rogue Cycling community in building the involvement of each member through Strava. This research uses case study method with qualitative descriptive research. The results showed that Rogue Cycling involving Strava's new media when analyzed using the concept of participatory culture (affiliations, expression, collaborative problem-solving, and circulation) had reached the four stages of participatory culture based on the formation of virtual Rogue Cycling community in Strava. Such as participated in upload cycling trails with members or carried out the circulation cycling trail process during cycling practice. The essence of participation through the support of the community concept and community involvement also shows that cycling activities cannot be done without a meeting, but virtual community activities and real communities make important contributions to the community.